2022
DOI: 10.3390/molecules27248641
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Colostrum Treatment of Specific Cancer Types: Current Evidence and Future Opportunities

Abstract: Worldwide, the incidence of cancer is on the rise. Current cancer treatments include chemotherapy, radiation therapy, and surgery. Chemotherapy and radiation treatment are typically associated with severe adverse effects and a decline in patients’ quality of life. Anti-cancer substances derived from plants and animals need to be evaluated therapeutically as it is cost-effective, have fewer side effects, and can improve cancer patients’ quality of life. Recently, bovine colostrum (BC) has attracted the interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…Specific constituents of BC, such as lactoferrin, CLA, and alpha-lactalbumin, have shown effectiveness in treating specific types of cancer. While BC has demonstrated anti-tumor properties in limited in vitro and animal studies, numerous BC components have shown the ability to induce apoptosis in cancer cells and limit tumor growth [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific constituents of BC, such as lactoferrin, CLA, and alpha-lactalbumin, have shown effectiveness in treating specific types of cancer. While BC has demonstrated anti-tumor properties in limited in vitro and animal studies, numerous BC components have shown the ability to induce apoptosis in cancer cells and limit tumor growth [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides lactoferrin, other substances may have anticancer activity. More recently, Alsayed [39] has summarized anticancer activity in the treatment of several bovine colostrum components, including lactoferrin, conjugated linoleic acid (CLA), and alpha-lactalbumin. Although their anticancer activity has been confirmed, other studies are required to evaluate the appropriate dosages of the drugs, their therapeutic effects, and their long-term safety.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the importance of colostrum, mainly BC, for farm animals is gaining popularity as a food ingredient [39] and as a nutraceutical for humans [40,41]. It is also being explored for potential applications in anti-tumor therapeutics for specific cancers [42]. Due to its nutritional value and low availability, BC has a high market value compared to other by-products of the sector [43], and its demand is projected to increase [44].…”
Section: Bovine Colostrum Transition Milk and Inter-species Variabilitymentioning
confidence: 99%